Can Physical Activity and Healthy Diet Help Long-Term Cancer Survivors Manage Their Fear of Recurrence? - Séguin Leclair, Caroline; Lebel, Sophie; Westmaas, J. Lee (Frontiers in Psychology, 2021)
Objective: Fear of cancer recurrence (FCR) adversely affects quality of life, but health behaviors such as physical activity (PA) and fruit and vegetable intake (FVI) may help alleviate FCR for some survivors. This cross-sectional study tested the Common-Sense Model (CSM) of FCR by investigating associations between constructs from the CSM (perceived illness consequences, control over health, cancer chronicity), and survivors’ health behaviors, health self-efficacy, and FCR. Methods: Using wave 3 data from the American Cancer Society Longitudinal Study of Cancer Survivorship-I, path analyses were conducted among mixed-cancer participants (N=2337) who were on average 8.8 mean years post-diagnosis. Results: A final good fitting model (χ2 = 38.12, p < 0.001; CFI = 0.99; RMSEA = 0.05) indicated that perceiving fewer illness consequences, and greater control over one’s health, were associated with higher PA (β = .15 and -.24, p <.01, respectively), and higher health self-efficacy (β = .24, -.38, p <.01, respectively). Perceiving higher cancer chronicity was associated with lower health self-efficacy (β = -.15, p <.01), and higher FCR (β = .51, p <.01). Both greater PA and FVI were associated with higher health self-efficacy (β = .10 and .11, p <.01, respectively) which in turn was associated with lower FCR (β = -.15, p <.01). Conclusions: Increasing survivors’ sense of control over health, decreasing perceived chronicity of the illness, and mitigating its consequences may increase their health behaviors and health self-efficacy, which in turn could decrease their FCR. Longitudinal and experimental studies are needed to confirm these findings.